Biodentine Counteracts the Aging Process of Human Dental Pulp Stem Cells Through Wnt/β-Catenin Pathway - Qi Zhang; Shujie Cao; Min Zhang; Daming Wu; Chengfei Zhang; Jin Li (International Dental Journal, 2025)
Objectives: This study aimed to evaluate the effects of Biodentine on human Dental Pulp Stem Cells (hDPSCs) proliferation and senescence and explore the underlying anti-aging mechanism. Methods: hDPSCs were isolated from two groups of patients aged 18 to 27 and 60 to 70 years and treated with Biodentine extract. The optimal concentration of Biodentine extract was determined using the CCK-8 assay. Biodentine treatment on hDPSCs proliferation and aging was assessed using qRT-PCR and Western blot. The small molecule inhibitor XAV939, targeting the Wnt/β-catenin signaling pathway, was added to investigate the anti-aging mechanism of Biodentine in hDPSCs. Results: The isolated hDPSCs exhibited mesenchymal stem cells (MSCs) characteristics, and the proportion of S-phased cells decreased significantly in the aged group. Biodentine promoted hDPSCs proliferation, with the most pronounced effect observed at 0.2 mg/mL. qRT-PCR showed that Biodentine enhanced the expression of odonto/osteogenesis-related genes. Senescence-associated β-galactosidase staining and Western blot analysis further demonstrated the significant anti-aging effect of Biodentine on hDPSCs. Western blot revealed that Biodentine exerted its anti-aging effect through the Wnt/β-catenin signaling pathway. Conclusion: The study demonstrated that Biodentine promotes proliferation and exerts anti-aging effects on hDPSCs through the Wnt/β-catenin pathway.